(untitled) (Research, Society and Development, 2024)
The purpose of this article is to address the context of scientific journal evaluation using citation indexes. This is a descriptive study that seeks to detail the particularities of the Impact Factor (IF), as well as to broaden the understanding of journal evaluation supported by citation indexes. The objectives of the study are: i) to describe the development of the IF; ii) to identify other bibliometric measures based on the number of citations; iii) to list points of attention that should be observed in scientific evaluation processes based on citation indexes; and iv) to identify alternative ways to use indexes formulated by large commercial scientific publishers. Despite the growing development of other citation indexes, it is not advisable to limit the evaluation of journals to these measures alone, given the diversity of factors that influence their results. As alternatives to the indexes published by commercial databases, some countries have proposed databases and indexes that more adequately evaluate their scientific production. The development of non-profit databases such as OpenALex is also noteworthy. In conclusion, it is understood that a cultural change is needed in the scientific community regarding the evidence used to evaluate research products. Those who carry out scientific evaluations supported exclusively by metrics must bear in mind that the precision granted by numerical results is only apparent. Therefore, the use of a set of analysis methods, paying special attention to peer review, is the most recommended.